2020
DOI: 10.1021/acs.jpcb.0c07935
|View full text |Cite
|
Sign up to set email alerts
|

Sum-Frequency Signals in 2D-Terahertz-Terahertz-Raman Spectroscopy

Abstract: We demonstrate that halogenated methane 2D-Terahertz Terahertz Raman (2D-TTR) spectra are determined by the complicated structure of the instrument response function (IRF) along ω 1 and by the molecular coherences along ω 2. Experimental improvements have helped increase the resolution and dynamic range of the measurements, including accurate THz pulse shape characterization. Sum-frequency exci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…The most recent interpretation of the TTR signals by Blake and coworkers suggested that the observed signal stems from the instantaneous excitation of intramolecular vibrations through a two-photon absorption process by a pair of strong THz fields (sum-frequency excitation pathway). 23 This explanation is consistent with the interpretation of the THz-Kerr effect observed earlier for similar liquids. [24][25][26][27] Our RTT pulse sequence lacks the strong initial THz process required for that process.…”
Section: Introductionsupporting
confidence: 92%
“…The most recent interpretation of the TTR signals by Blake and coworkers suggested that the observed signal stems from the instantaneous excitation of intramolecular vibrations through a two-photon absorption process by a pair of strong THz fields (sum-frequency excitation pathway). 23 This explanation is consistent with the interpretation of the THz-Kerr effect observed earlier for similar liquids. [24][25][26][27] Our RTT pulse sequence lacks the strong initial THz process required for that process.…”
Section: Introductionsupporting
confidence: 92%
“…The most recent interpretation of the TTR signals by Blake and coworkers suggested that the observed signal stems from the instantaneous excitation of intramolecular vi-brations through a two-photon absorption process by a pair of strong THz fields (sum-frequency excitation pathway). 23 This explanation is consistent with the interpretation of the THz-Kerr effect observed earlier for similar liquids. [24][25][26][27] Our RTT pulse sequence lacks the strong initial THz process required for that process.…”
Section: Introductionsupporting
confidence: 92%
“…[38][39][40][41] Furthermore, the double peak structure of the cross peak, or correspondingly, the beating of the time-domain data in the t 2 -direction, emphasize that the response is not instantaneous in the THz dimension in our RTT pulse sequence, unlike for the TTR pulse sequence. 23 The demonstrated sensitivity of 2D Raman-THz spectroscopy toward lowfrequency intra/intermolecular vibrational couplings can be utilized further to study structural characteristics of hydrogen bond network forming systems.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional vibrational spectroscopy is a versatile technique to study microscopic interactions at their natural, femtosecond time scales. 1 Recently, a series of hybrid spectroscopic experiments [2][3][4][5] involving mid-infrared, far-infrared (or terahertz), and visible (Raman) pulses have been developed to study electrical and mechanical anharmonicities, [6][7][8][9] structural heterogeneities of liquids, [10][11][12] and the couplings between intermolecular and intramolecular vibrational modes. 13,14 However, the interpretation of such spectra is still an open question and requires adequate simulation methods.…”
Section: Introductionmentioning
confidence: 99%